Visual Outcome and Complications in Ab-Externo Scleral Fixation IOL in Aphakia - Muhammad Nasir Bhatti, Azizur Rahman, Israr Ahmed Bhutto, Sadia Bukhari Mazharul Hassan (Pakistan Journal of Ophthalmology, 2011)
Purpose: To assess the visual outcome and complications in patients after Ab-externo scleral fixation of intraocular lens. Materials and Methods. This quasi experimental study was conducted at Isra Postgraduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital, Malir, Karachi; from May 2006 to April 2007. Study included total 30 eyes of 30 patients fulfilling criteria. All cases were worked up according to the protocol. All patients underwent Ab-externo scleral fixation of IOL. Patients were followed up at 1st day, 1st week, 1st month, 2nd month and 3rd month. Complete eye examination including best-corrected visual acuity and complications were noted on each visit. Results: Best corrected visual acuity improved in 29 (96.7%) patients while 26 (86.7%) patients showed BCVA 6/12 or better. The most common intraoperative and postoperative complications observed were vitreous hemorrhage and astigmatism respectively. Conclusion: Ab-externo scleral fixation of an IOL was found to be safe and showed favourable postoperative results.